Disease-Modifying Effects of Long-Term and Continuous Use of Nonsteroidal Anti-Inflammatory Drugs (NSAIDs) in Spondyloarthritis - Rebecca S. Y. Wong (Advances in Pharmacological Sciences)
Spondyloarthritis or spondyloarthropathy (SpA) is a group of related rheumatic disorders, which presents with axial and nonaxial features, affecting structures within the musculoskeletal system, as well as other bodily systems. Both pharmacological and nonpharmacological therapeutic options are available for SpA. For decades, nonsteroidal anti-inflammatory drugs (NSAIDs) have been used as the first-line drugs to treat the disease. Research has shown that other than pain relief, NSAIDs have disease-modifying effects in SpA. However, to achieve these effects, continuous and/or long-term NSAID use is usually required. This review will give an overview of SpA, discuss NSAIDs and their disease-modifying effects in SpA, and highlight some of the important adverse effects of long-term and continuous NSAID use, particularly those related to the gastrointestinal, renal, and cardiovascular systems.